Diet composition of Esox lucius Linnaeus, 1758 in Salmanlı Dam Lake, Türkiye - Sibel Alagöz Ergüden; Anıl Alper Aydın; Deniz Ayas; Deniz Ergüden (Universitas Malikussaleh, 2026)
The present study investigated the seasonal feeding habits of the pike (Esox lucius) inhabiting Salmanlı Dam Lake in the Adapazarı district of Sakarya province. Sampling was conducted on a regular basis over the course of three seasons (spring, summer and autumn) during the 2024–2025 period. The method employed was spin fishing from the shore. In accordance with the regulations prohibiting fishing in the lake during the winter months, specifically from December to March, no sampling could be conducted during this period. Consequently, no samples were obtained. A total of 267 pike individuals were captured during the study period, and their stomach contents were analysed. A thorough analysis of the stomach contents revealed that the diet of E. lucius consisted of various types of fish (Atherina boyeri, Alburnus escherichii, Cyprinus carpio, Scardinius erythrophthalmus), reptiles (Natrix natrix, Lacerta viridis), amphibians (Pelophlax sp.), rodents (Microtus sp.), and macroinvertebrates. Despite the preponderance of fish in the diet throughout the study period, the reptile species N. natrix was dominant, particularly in spring and autumn. This finding suggests that pike may modify their feeding habits in response to seasonal changes in prey availability. The results obtained demonstrate the feeding flexibility and adaptive behaviour of pike to environmental stressors, thus contributing to a more complete understanding of the dynamics of the local ecosystem. Keywords: Diet Composition; Esox lucius; Stomach Content Analyses; Reservoir; Sakarya; Türkiye